Prime Minister Decree No. 2814 Of The Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
Thursday, the 4th of September, 2025 (Gregorian Calendar), corresponding to the 12th of Rabie I, 1447 (Islamic Calendar) shall be deemed an official paid holiday for the workers in the ministries, governmental departments, public authorities, local administrative units, public sector companies, and public business sector companies, on the occasion of Al Mawlid Al Nabawi (the celebration of Prophet Muhammad's birth).